Is It High Time to Redefine the Legal Framework on Cohabitation in Family Law? - Nana Weber (LeXonomica, 2024)
Cohabitation is an institution of Slovenian family law quite similar in effect to marriage in that it creates the same rights and obligations. However, unlike marriage, its existence must be proved in each individual proceeding separately which creates difficulties, particularly in practice. This situation is exacerbated by the fact that the existence of cohabitation in the Slovenian Family Code is defined exclusively using rather vaguely defined legal standards. In this article, the author gives an overview of the current relevant case-law of Slovenian courts on cohabitation and discusses the possibilities for future legal regulation of the establishment of this community.PovzetekZunajzakonska skupnost je institut slovenskega družinskega prava, ki je po svojih učinkih zelo podoben zakonski zvezi, saj ustvarja enake pravice in obveznosti. Vendar pa je za razliko od zakonske zveze njen obstoj treba dokazovati v vsakem posameznem postopku posebej, kar v praksi povzroča težave. Te težave dodatno poglablja dejstvo, da je obstoj zunajzakonske skupnosti v slovenskem Družinskem zakoniku opredeljen z uporabo precej ohlapno določenih pravnih standardov. Avtorica v prispevku podaja pregled aktualne relevantne sodne prakse slovenskih sodišč glede zunajzakonske skupnosti ter obravnava možnosti za njeno prihodnjo pravno ureditev.